Methylisothiazolinone contact allergy in Croatia: Epidemiology and course of disease following patch testing - Hadzavdic, Suzana Ljubojevic; Uter, Wolfgang; Samoscanec, Maja Ilijanic; Johansen, Jeanne D. (Contact Dermatitis, 2018)
BACKGROUND: Methylisothiazolinone (MI) caused an epidemic of contact allergy in Europe, as shown by data from many countries, but no studies from Croatia exist. Also, data are lacking on the severity of allergic contact dermatitis (ACD) caused by MI, and its impact on quality of life and prognosis. OBJECTIVES: To determine the frequency of MI contact allergy among Croatian dermatitis patients, identify causative exposures, assess the impact of disease, and study the prognosis. METHODS: Data were collected for consecutive dermatitis patients with MI contact allergy patch tested in Croatia between November 2, 2015 and November 3, 2016. RESULTS: MI contact allergy was diagnosed in 13.2% of 798 tested patients. The most frequent dermatitis locations were the hands (76%) and face (61%). In 89.3% of patients, MI contact allergy was found to be of current relevance. Considerable severity and impact on daily life of disease was found at the first consultation, but this significantly decreased until follow-up 3 months later. CONCLUSIONS: Patch testing is the standard method for the diagnosis of ACD, and it has been shown to have an important beneficial effect on prognosis. The severity of MI ACD and the impact on daily life emphasize the need for prevention.
EVALuna2:35663